Detecting local undo conflicts in multi-user CAD. Issue 6 (1st November 2016) - French, David J.; Wilcox, Scot; Tew, Kevin; Red, Ed
ABSTRACT: Multi-user computer-aided design (CAD) is an emerging technology that facilitates collaboration by allowing users to work on the same design at the same time. This paper provides a classification of the types of conflicts that can occur during the use of local undo in multi-user CAD, and describes a method for detecting those conflicts. This method can be used to prevent and warn the user about undo conflicts as well as provide users with information about the cause of the conflict so they can collaborate to resolve it. This method has been successfully implemented and tested in Brigham Young University's NXConnect multi-user CAD prototype. GRAPHICAL ABSTRACT: